Kompleksinės mokslinės techninės programos ir informaciniai poreikiai (rusų k.) - Atkočiūnienė, Zenona; Broniukaitis, Romualdas (Knygotyra, 1988)
The peculiarities of modern social development have determined the increase in national economy management and planning standards. Complex scientific and technical programs serve the timely and effective solution of major social and economic problems.In this connection, the chief task of all state systems of scientific and technical information (TI) links is to supply information for objective complex programs.The most worthwhile and effective means to supply the objective complex programs with information is to establish problem-oriented data banks (PODB).The article points out the major shortcomings in the existing methods of information requirements (IR) study from the point of view of PODB establishment: PODB can be initiated only after work on the objective complex program has begun.The prognostication of information required by the complex scientific and technical programs' executors is the first step in the establishment of PODB. Its aim is to determine the thematic boundaries of the particular database using the information carried by planning projects and obtained through the opinions of planning bodies and program executors.